2020
DOI: 10.34154/2020-ejcs-0201-10-19/euraass
|View full text |Cite
|
Sign up to set email alerts
|

An update on the effectiveness of metformin alone and with chemotherapy drugs on tumor cells

Abstract: Cancer and diabetes are critical risks that reveal many complications. Metformin has long been used in herbal medicine as an anti-diabetes medicine. It is one of the first-line therapies for type two (T2D that has gained use across different healthcare systems. It is the most preferred form of treatment due to its safety, being readily available, and widely used because it has fewer and affordable side effects for many users. The repurposing of metformin used in other treatments to treat cancer patients or the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…Increased mTOR signaling activity has been associated with prostate, brain, lung, bladder, and kidney cancers. The epidermal growth factor (EGF) is thought to be downstream of the mTOR pathway [31]. Another research study indicated that the treatment of SK-MEL-28 melanoma cells with PXT and MET for 24 h resulted in the activation of AMPK and the mTOR pathway downstream [32].…”
Section: Discussionmentioning
confidence: 99%
“…Increased mTOR signaling activity has been associated with prostate, brain, lung, bladder, and kidney cancers. The epidermal growth factor (EGF) is thought to be downstream of the mTOR pathway [31]. Another research study indicated that the treatment of SK-MEL-28 melanoma cells with PXT and MET for 24 h resulted in the activation of AMPK and the mTOR pathway downstream [32].…”
Section: Discussionmentioning
confidence: 99%